Sistema atende mulher: sistema de informação no centro de referência da mulher Ednalva Bezerra - Cortes, Gisele Rocha [UNESP]; Araujo, Wagner Junqueira de; Silva, Douglas Limeira (Universidade Federal de Campina Grande, 2014)
The physical, psychological, sexual, moral and patrimonial violence affects women of different ages, social classes, ethnic and racial groups, levels of education and religion, all over Brazil. One of the obstacles in the strategies of prevention and facing violence against women, in public care services, focuses on the absence of an information system, automation of data and care flows. The existence of reliable data is essential for performing diagnoses, goals and conducting research on women in situations of violence who access the service agencies. In this sense, the goal of research is to present the experience of implementing a policy of data management called Woman System, in Ednalva Bezerra Women's Reference Center, which offers host/psychological and social care, guidance and legal referral for women that face any violence situation. As methodological paths, we adopt research in action. In our analyzes, we found that in this kind of public service, the use of the data system may improve the full and humanized care to women in situations of violence. Thus, the System Woman Care, still a developing phase, appears to improve the flow of relevant information within the institution, driving a process of knowledge, decision-making and intervention against gender violence.

Um dos grandes desafios nas ações de prevenção e combate à violência contra as mulheres, no âmbito dos órgãos de atendimento, a exemplo do Centro de Referência da Mulher Ednalva Bezerra (CRMEB), foco desta pesquisa, incide na ausência de um sistema de informação, de automação, de padronização na classificação dos dados e fluxos de atendimento. O objetivo da pesquisa é apresentar a experiência de implantação de uma política de gestão informacional a partir de um sistema de automação dos dados de atendimento do CRMEB. Como caminhos metodológicos, adotamos a pesquisa-ação. Em nossas análises, verificamos que, no CRMEB, a utilização do Sistema Mulher contribui para o atendimento integral e humanizado às mulheres em situação de violência. Conclui-se que, no mundo atual, onde cada vez mais organizações dependem da informação que produzem de forma rápida e eficiente, torna-se premente a implementação de técnicas e de políticas concentradas, que convirjam no sentido de garantir a perenidade e a acessibilidade a este tipo de informação. Sendo assim, o sistema de informação, em desenvolvimento no CRMEB, surge para aperfeiçoar o fluxo de informação relevante no âmbito da instituição, desencadeando um processo de conhecimento e de tomada de decisão e intervenção perante a violência de gênero.
Woman meets system: Information system reference center on women Ednalva Bezerra
Keywords: Information; Data system; Violence against women; Women's reference center; Sistema de informação; Gestão da informação; Violência contra mulheres; Centro de referência da mulher